Inventory Application Using Reorder Point Method: Study On One Of The Knitted Textile Companies - Suciyono, Nanang; Perdiansah, Erwin (LPPM STMIK Mardira Indonesia, 2025)
The research findings indicate that the design of the Android-based Smart Tourism application at Dangiang Cibeger Nature Tourism, Garut Regency, aims to enhance the quality of tourism services by utilizing digital technology. In the contemporary digital age, mobile applications serve as a valuable means of disseminating information, promoting tourism, and facilitating the efficient and modern management of tourism locations. The findings of this study demonstrate that the deployment of the Smart Tourism application offers substantial benefits for both travelers and tourism management. This program provides tourists with access to information, aids in travel planning, and enhances the overall tourism experience. Simultaneously, for tourism administrators, the application serves as a potent promotional tool, enhancing tourist attendance and providing data for assessment and future tourism development. This research illustrates that the Smart Tourism application can serve as an innovative solution for technology-driven tourism management and development. With effective execution, this application can enhance the allure of Dangiang Cibeger, draw more tourists, and promote the sustainability of tourism in the Garut Regency. Consequently, the evolution and maintenance of this application must continue to align with technological advancements and the evolving needs of travelers.